AN ANALYSIS OF THE EFFECTS OF BUDGET MANAGEMENT QUALITY, HUMAN CAPITAL, AND CROSS-SECTOR COLLABORATION ON STUNTING FINANCING WITH GOOD GOVERNANCE AS A MEDIATING VARIABLE AT COMMUNITY HEALTH CENTERS IN TIMOR TENGAH SELATAN REGENCY - Desti Lambe; I Komang Arthana; Paulina Yuritha Amtiran (RADJA PUBLIKA, 2026)
This study aims to analyze the effect of budget management quality and human capital on stunting financing, with good governance as a mediating variable at public health centers in Timor Tengah Selatan Regency. The research adopts a quantitative explanatory approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS), involving 143 respondents from 37 public health centers.The results indicate that human capital and good governance have a positive and significant effect on stunting financing, while budget management quality does not have a direct significant effect. However, budget management quality significantly influences good governance. Furthermore, the mediation analysis reveals that good governance significantly mediates the relationship between budget management quality and stunting financing, but does not mediate the relationship between human capital and stunting financing. These findings highlight that the effectiveness of stunting financing is not solely determined by budget management quality, but is more strongly influenced by human resource capacity and the implementation of good governance principles. This study contributes to the literature on public financial management and health policy, particularly in strengthening governance and human capital at the local health service level.